2004
DOI: 10.4049/jimmunol.172.10.6382
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of C5a Anaphylatoxin by a Peptide That Is Complementary to a Region of C5a

Abstract: PL37 (RAARISLGPRCIKAFTE) is an antisense homology box peptide composed of aa 37–53 of C5a-anaphylatoxin and is considered to be the region essential for C5a function. Using a computer program, we designed the complementary peptides ASGAPAPGPAGPLRPMF (Pep-A) and ASTAPARAGLPRLPKFF (Pep-B). Pep-A bound to PL37 and to C5a with very slow dissociation as determined by analysis using surface plasmon resonance, whereas Pep-B failed to bind at all. C5a was inactivated by concentrations of 7 nM or more of Pep-A, and thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 19 publications
1
24
0
1
Order By: Relevance
“…Therefore, we generated complementary peptides to PL37 with the software program MIMETIC (4), based on its previous success at generating complementary peptides inhibitory to HIV-1 reverse transcriptase (4,12) and thrombomodulin (20). PepA, one of the complementary peptides targeting PL37, has shown an appreciable capacity to interfere with C5a function (10). The sequence of PL37 was that of human C5a, and the amino acid sequence homology to the corresponding portion of rat C5a was 56%.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we generated complementary peptides to PL37 with the software program MIMETIC (4), based on its previous success at generating complementary peptides inhibitory to HIV-1 reverse transcriptase (4,12) and thrombomodulin (20). PepA, one of the complementary peptides targeting PL37, has shown an appreciable capacity to interfere with C5a function (10). The sequence of PL37 was that of human C5a, and the amino acid sequence homology to the corresponding portion of rat C5a was 56%.…”
Section: Discussionmentioning
confidence: 99%
“…Since the co-addition of C3a did not significantly potentiate cysLT generation when compared with IgE and anti-IgE antibody alone, it remains to be determined whether acetylated peptide A precisely antagonized C3a activity. This peptide has been shown to inhibit the action of C5a in human neutrophils, in a human cell line, and in an in vivo C5a-induced rat shock model (10). Since this novel C5a inhibitor appears to inhibit the C5a reaction in human lung tissues, it may be useful for suppressing allergic inflammation in human lungs.…”
Section: Resultsmentioning
confidence: 99%
“…Human purified IgE and goat anti-human IgE antibody were purchased from Chemicon International (Temecula, Calif., U.S.A.). A complementary peptide of C5a named as Pep A (ASGA-PAPGPAGPLRPMF) is a complementary peptide to amino acids 33 to 53 of human C5a (6,10,12). Its Nterminal alanine was acetylated and named as acetylated Pep A, as reported elsewhere (Asai et al, in submission).…”
Section: Methodsmentioning
confidence: 99%
“…Previous demonstration showed that the classical complement pathway was also activated on the surface of human islets that reacted with ABO-compatible blood involving IgG, IgM and other complement proteins, namely C3, C4 and C9, thus emphasizing the significance of immunoglobulins in the activation of complement cascade 23 . In contrast to other complement proteins, C5a has been proposed as a critical molecule responsible for the initiation of coagulation and inflammation by intervening TF expression in neutrophils 24,25 . Compstatin -a complement inhibitor treatment significantly improved the graft survival under in vivo conditions 26 .…”
Section: Hurdles Faced During Pancreatic Islet Transplantationmentioning
confidence: 99%